The Correlation Between Of Nutritional Status And Cognitive Development - INNA SHOLICHA FITRIANI (Jurnal Keperawatan)
Nutrition becomes an important part in the role of mental and physical health for toddlers. In Ponorogo there are three villages with a population of the majority are living with down syndrome, one of them is sidoharjo village, Jambon, with 323 people where toddlers till adult 40 years has the most Down Syndrom attact. One of  factor that coused down syndrome is the low coverage of nutrition that impact on the level of intelligence.